VALUE-ADDED OF CORN FRITTERS ON SUPER SWEET CORN BUSINESS GIAN F1 IN AKABILURU DISTRICT, LIMA PULUH KOTA REGENCY - Mega Amelia Putri (Universitas Teuku Umar, 2022)
Gian F1's super sweet corn business produces several processed sweet corn, one of which is corn fritters as its main product with a production capacity of 50 kilograms per day. The purpose of this study was to explain the process of making corn fritters and analyze the value added of corn fritters. The research was conducted in December 2021. The method applied was the case study method and the data analysis used to analyze the value added was the Hayami method. The results of the study explained that the value added of Gian F1's corn fritters products was high. This is because the value added ratio of corn fritters by Gian F1's business exceeds 40%, which is 67.26%. These results indicate that the corn fritters products from Gian F1's business are feasible to be maintained and developed.